(untitled) (The Indian Veterinary Journal, 2024)
The editorial team wishes to thank the thousands of veterinary and animal husbandry sciences professionals, practicing veterinarians, teachers, students and other research/education/ expertise community for your unstinted support in bringing out the prestigious international journal continuously .